The Analysis of Differences and Similarities of Eastern and Western Women’s Images in Liang Sanbo Yu Zhu Yingtai and Romeo and Juliet Novel - Yenny Yenny (Lingua Cultura, 2010)
Sanpek Engtay and Romeo Juliet are the two famous classic love novels from Eastern and Western countries. They are liked by many generation of eastern and western readers. Both novels describe the image of women at each decade. Engtay represents the image of women at feudalism era while Juliet represents it Renainsance era. In this article, the writer did research at education, marriage, love, women's personality, and women's position at each decade. Library research was done in this study with the purpose of letting people know the differences and similarities of women's images between those two decades It can be concluded that in both writings, they have some similarities when describing love, mindset, and women's personality. The differences are about education, marriage, and women's position at feudalism and Renainsance decades.